Repurposing of Ribavirin for the treatment of anticancer by using in silico molecular docking (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
There is a prolonged process involved in discovering and developing new treatments for cancer diseases which is costly. However, drug repurposing provides an effective way of determining new uses of approved drugs. This study will assess the ability of Ribavirin to act as an antineoplastic compound through in-silico molecular docking. Methods: The 3D crystalline structures of critical cancer-associated proteins, such as eukaryotic translation initiation factors Thymidylate Synthase (TS), eIF4E (Translation Initiation), CDK4, IMPDH2 (Inosine Monophosphate Dehydrogenase), BRAF V600E Kinase, Cyclin-Dependent Kinase (CDK), Ribonucleotide Reductase or ERK2, Topoisomerase, Kinase protein were retrieved from the Protein Data Bank (PDB). Ligand preparation of ribavirin was conducted, followed by grid generation and molecular docking utilizing standard computational software to predict optimal binding conformations. The in-silico profiling demonstrated that ribavirin successfully binds to the active site residues of the targeted proteins through critical hydrogen bonding and van der Waals interactions. The results values are 1TUP (-6.578), 1NF7(-7.078), 4UND (-7.1), 1HVY (-6.13), 4MAN (-5.561), 4WTG (-7.156), 3OCB (-6.402), 3VHE (-6.276), 1U72(-8.19), 5TC3(-6.333). "The molecular docking analysis revealed a strong binding affinity of -8.19kcal/mol for 1U72 (NPC). The obtained results from molecular docking confirm the possibility of using ribavirin as an anticancer drug candidate. The positive interaction of ribavirin with the target protein is evidence enough to test its anticancer activity experimentally.
Keywords: Ribavirin; Drug Repositioning; Molecular Docking; Anticancer; eIF4E